The relationship between English language educators’ digital literacy and their sense of self-efficacy - Zhakupova, A. (MAQSUT NARIKBAYEV UNIVERSITY School of Liberal Arts. Astana, 2025)
This quantitative study analyzes the relationship between English language educators’ digital literacy and their sense of self-efficacy in higher education institutions in Astana, Kazakhstan. The research aims to examine whether digital literacy is correlated with and predictive of English language educators’ self-efficacy. An online survey incorporating modified versions of the Digital Literacy Scale and the Teachers’ Sense of Efficacy Scale (TSES) was used to collect data. Participants included 52 in-service English language educators at higher educational institutions in Astana. The data were analyzed through Pearson correlation and multiple linear regression analysis. The results showed statistically significant, moderate-to-strong positive relationship between the two variables. Digital literacy further was demonstrated to be a significant predictor of self-efficacy by multiple linear regression analysis, even after controlling for sociodemographic factors such as age and teaching experience. The results suggest that encouraging digital competence may contribute to increased instructional confidence among university educators. While the study offers valuable insights into a relatively under-researched population, it is geographically limited to Astana. Future research with larger and more diverse samples across Kazakhstan is recommended. The study contributes to ongoing efforts to enhance digital integration and professional development in higher education.
Keywords: digital literacy, self-efficacy, English language educators, higher education